Age-Specific Effectiveness of an Oil-in-Water Adjuvanted Pandemic (H1N1) 2009 Vaccine Against Confirmed Infection in High Risk Groups in England - Andrews, Nick (Oxford University Press, 2011)
Background. The use of a squalene-containing (AS03) pandemic vaccine for high-risk groups in England allowed vaccine effectiveness (VE) of such novel oil-in-water adjuvanted vaccine to be evaluated. Methods. Cases of laboratory-confirmed pandemic (H1N1)2009 influenza in England between November 2009 and January 2010 were followed up for history of pandemic (H1N1)2009 or 2009/10 seasonal influenza vaccination and relevant comorbidities. Controls were patients similarly tested but negative for the virus. We estimated pandemic (H1N1)2009 VE from the relative reduction in the odds of confirmed pandemic (H1N1)2009 infection between vaccinated and unvaccinated individuals after adjustment for confounders. Results. A total of 933 cases and 1220 controls were analyzed. VE from ≥14 days was 62% (95% CI 33% to 78%) with protection from 7 to 13 days post-vaccination (59%, 95% CI 12% to 81%). VE from ≥14 days differed by age (P=.03) being 77% (11% to 94%) in children <10 years, 100% (80% to 100%) in 10–24-year olds, 22% (-153% to 76%) in 25–49-year olds, and 41% (-71% to 80%) in 50-plus-year-olds. Conclusion. Use of oil-in-water adjuvant contributed to a high VE with reduced antigen dosage in children and young adults. Our VE estimate supports the serological correlates of protection used for licensure in these age groups. However, the immunological basis of disappointing VE in older adults merits investigation.